Imaging mass spectrometry for assessing temporal proteomics: Analysis of calprotectin in Acinetobacter baumannii pulmonary infection. Issue 7 (24th July 2013) - Moore, Jessica L.; Becker, Kyle W.; Nicklay, Joshua J.; Boyd, Kelli L.; Skaar, Eric P.; Caprioli, Richard M.; Lodeiro, Carlos; Martínez, José Luis Capelo; Santos, Hugo M.
<x xml:space="preserve">Abstract</x> Imaging MS is routinely used to show spatial localization of proteins within a tissue sample and can also be employed to study temporal protein dynamics. The antimicrobial S100 protein calprotectin, a heterodimer of subunits S100A8 and S100A9, is an abundant cytosolic component of neutrophils. Using imaging MS, calprotectin can be detected as a marker of the inflammatory response to bacterial challenge. In a murine model of Acinetobacter baumannii pneumonia, protein images of S100A8 and S100A9 collected at different time points throughout infection aid in visualization of the innate immune response to this pathogen. Calprotectin is detectable within 6 h of infection as immune cells respond to the invading pathogen. As the bacterial burden decreases, signals from the inflammatory proteins decrease. Calprotectin is no longer detectable 96–144 h post infection, correlating to a lack of detectable bacterial burden in lungs. These experiments provide a label‐free, multiplexed approach to study host response to a bacterial threat and eventual clearance of the pathogen over time.